Cover Image. (13th November 2020) - Nolot, Emmanuel; Mazel, Yann; Barnes, Jean‐Paul; Sabbione, Chiara; Navarro, Gabriele; Tempez, Agnes; Legendre, Sébastien
Abstract : The cover image is based on the ECASIA Special Issue Paper Accelerating the development of phase‐change random access memory with in‐fab plasma profiling time‐of‐flight mass spectrometry by Emmanuel Nolot et al., https://doi.org/10.1002/sia.6823 .